Managemen Perilaku Organisasi untuk Meningkatkan Kinerja Guru - Karmiati, Karmiati; Suparjo, Suparjo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Teachers play a central role in determining the quality of education in schools because they are directly involved in the learning process. Optimal teacher performance is influenced not only by individual abilities, but also by organisational factors that shape teacher work behaviour. This article aims to analyse the role of organisational behaviour management in improving teacher performance in schools. This study uses a qualitative approach with a case study design conducted at SMP Negeri 1 Purwojati. Data were collected through observation, interviews, and documentation, then analysed descriptively. The results of the study show that work motivation, principal leadership, collaborative work culture, a conducive school climate, and a reward system contribute significantly to shaping positive teacher behaviour. Effective organisational behaviour management has been proven to improve teachers' professionalism, commitment, and quality of learning services. These findings emphasise the importance of the role of school management in designing strategies to continuously improve teacher performance in order to support the quality of education.